An environmentally benign dual action antimicrobial: quaternized chitosan/sodium alga acid multilayer films and silver nanoparticles decorated on magnetic nanoparticles. Issue 14 (21st September 2016) - Jin, Feng; Xiang, Qian; Chen, Xiaoqin; Peng, Xuefeng; Xing, Xiaodong
Abstract: There is an urgent need to develop a puissant and environmentally benign antibacterial composite that act via multiple mechanisms to make response to the potentially daunting complexity of the microbial population and microbial antibiotic resistance. In this work, a facile and green approach, layer-by-layer self-assembly technology was applied to assemble polycation quaternized chitosan (QAC) and polyanion sodium alga acid onto magnetic nanoparticles (MNPs). Then silver nanoparticles (AgNPs) with stable and narrow-sized distribution in the range of 25–35 nm were immobilized on the surface of MNPs with L-ascorbic acid as reducing agent and organic multilayers as stabilizer. Through above modification on MNPs, we expected to achieve a green dual antibacterial and recyclable composite via the combined antibacterial action of QAC and AgNPs. Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, transmission electron microscopy, zeta potentials, and dynamic light scattering were employed to confirm the success of the surface functionalization. Silver ion release process was detected by inductively coupled plasma mass spectrometry. Furthermore, the antibacterial properties of the biomaterials against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus were studied. The modified MNPs exhibited rapid, efficient, and long-lasting biocidal abilities against E. coli and S. aureus . The magnetic antibacterial composite still showed excellent antibacterial efficiency during five exposure/collection/recycle procedures.